SUBOPTIMAL INVESTMENTS AND M&A DEALS IN EMERGING CAPITAL MARKETS - Cherkasova, Victoria; Zakharova, Evgeniya (Economic Annals, 2016)
This paper focuses on the efficiency of target-company investment decisions before and after Merger & Acquisition deals. We study whether M&A deals help to solve the problem of suboptimal investment after the acquisition. Using a sample of 145 target companies from BRICS countries that were acquired during the period 2004-2014, we outline those that had over- or underinvested before the deal and show that more than half the companies managed to optimize the investment level after the deal. We determine the key factors that improve the inefficiency of investment decisions and demonstrate that the industry and country have an impact on the degree of suboptimal investment.